Article Review: The Potential Of Plants In The Zingiberaceae Family As Agents For Treating Acute Inflammation - Yulianti Novita Sari; Desi Nadya Aulena; Yovieta Nenda Ghani; Fachrul Shihab Al Qardhawi; Pebri Hidayat; Natasya Aulia Bahri; Faqine Ascory Sunargo; Galuh Ayu Adelyda Bahri; Olivia Yuli Suhardi; Adinda Farah Salsabila Nasution; Minarta Agustin Silitonga; Sabrina Putri Maharani; Aji Shalih Niskala (Journal of Natural Product for Degenerative Diseases, 2026)
Background: Anti-inflammatory drugs suppress the inflammatory process. Common therapies use NSAIDs, but long- term use can cause side effects such as stomach and kidney disorders and an increased risk of cardiovascular disease, as well as cost constraints. Therefore, alternatives from natural ingredients with fewer side effects are needed, one of which is plants from the Zingiberaceae family, which are still widely used traditionally without adequate scientific evidence, so their effectiveness and safety are not yet fully recognized in modern healthcare systems. Literature search was conducted systematically through several scientific databases, namely PubMed, ScienceDirect, Google Scholar, and Semantic Scholar, with a maximum publication time limit of 10 years. Methods: Article data included species, plant parts, types of extracts/active compounds, inflammatory test models, doses, and inflammatory inhibition results. Data were analyzed descriptively to compare the potential between Zingiberaceae genera. Results: In vivo tests showed that bioactive compounds such as curcumin, 6-gingerol, and zerumbone inhibit inflammatory mediators such as nitric oxide (NO) and pro-inflammatory cytokines (TNF-α, IL-1β, IL-6), as well as suppressing the expression of key enzymes iNOS and COX-2 through the NF-κB and MAPK signaling pathways. In in vitro testing, extracts from these plants were able to significantly reduce swelling (edema), with species such as kecombrang (Etlingera elatior) showing inhibition rates of up to 82.29%, almost equivalent to the standard drug sodium diclofenac. Conclusion: The Zingiberaceae family has strong potential as an acute anti-inflammatory agent through the inhibition of key inflammatory mediators and pathways; however, further standardization and clinical trials are still required.